STRATEGI KEPALA MADRASAH DALAM REKRUTMEN PESERTA DIDIK BARU DI MTs. MASHLAHIYAH KRECEK BADAS KEDIRI - Artdiatin; Mujiono (Jurnal Tarbiyah Almuslim, 2023)
The results of the study show that: 1) The strategy for recruiting new students is carried out by the MTs head. MashlahiyahKrecek: (a) Internal Strategy, namely by utilizing Human Resources to improve school facilities and infrastructure. (b) External strategy, namely by utilizing banner recruitment media, brochures and their accessories, website visits to schools, and coordination with related agencies. Recruitment for new student admissions is carried out by forming committees, compiling student procedures and requirements, announcements, receiving files, verifying and class placement. 2). Supporting factors include: teaching staff, school existence, geographical location and school performance while inhibiting factors are incomplete computer facilities and websites, as well as the number of institutions around the madrasa, and distance